The Landscape of Microbial Composition and Associated Factors in Pancreatic Ductal Adenocarcinoma Using RNA-Seq Data - Yu, Dong; Wang, Tengjiao; Liang, Dong; Mei, Yue; Zou, Wenbin; Guo, Shiwei (Frontiers in Oncology, 2021)
Recent researches on interrogation of the tumor microbiome (including bacteria, viruses, and fungi) has yielded important insights into the role of microbes in carcinogenesis, therapeutic responses, and resistance. Once thought to be a sterile organ, a number of studies have showed the presence of microbes within this organ in PDAC status. A microbiome-pancreas axis for PDAC carcinogenesis is proposed. However, it is unclear about the microbial composition of localized PDAC tissue. The associations between microbiome and PDAC reported in previous studies were detected in an indirect way, which mostly used samples from stool, oral saliva and intestinal samples. This study integrated 582 samples derived from PDAC tissues across 4 datasets, and presented a landscape of tumor microbiome at genus level in PDAC based on remining of RNA-Seq data. On average, there are hundreds of genera distributed in PDAC tissue, and dozens of core microbiota were identified by PDAC tissue. The pan-microbiome of PDAC tissue was also estimated, which might surpass 2500 genus. In addition, sampling sites (stroma vs. epithelium) and tissue source (human tissue vs. PDX) were found to have great effects on the microbial composition of PDAC tissue, but not the traditional risk factors (sex and age). It is the first study to focus on exploring the microbial composition of PDAC tissue, and is helpful to have a deep understanding of tumor microbiome. The identified specific taxa might be potential biomarkers for follow-up researches.